NONPHARMACEUTICAL AND PHARMACEUTICAL COVID-19 PREDICTION MODELS - Okwonu, Friday Zinzendoff (FUDMA Journal of Sciences, 2024)
Global tourism and leisure came to hurt due to the Covid-19 pandemic. The ways we lived our lives was automatically truncated due to the fear of the virus of unknown etiology. We started adjusting to new lifestyle. Community life came to hurt due to lockdown to curtail the spread of the virus. Various forms of non-pharmaceutical approaches (NPA) or intervention (NPI) was adopted in the absence of vaccine. As time progresses different vaccine became available (Pharmaceutical approach {PA)) was discovered to mitigate the spread of the virus. To reassure the safety of people, different levels of social distancing values in meters was applied due to the fear that the virus was airborne.  This study tends to investigate whether onset data from the NPA and PA interventions could be used to predict the probability of infection thereby bringing the spread of the virus to a hurt. The analysis based on these prediction models revealed that both the NPA and the PA are very effective in mitigating and hurting the spread of the virus. The PA prediction model revealed that as more people are vaccinated with time, the probability of infection reduces drastically thereby increasing the probability of social mingling. Therefore, we concluded that these data independent prediction models are useful to predict the likely outcome of infection of the disease of unknown etiology based on the onset data.
Keywords: Non-pharmaceutical approaches; Pharmaceutical approach; Covid-19; Prediction models